An Exploration of Parents’ Experiences about Early Childhood Education in Primary Schools - Alia Bibi; Dr. Muhammad Zafar Iqbal; Dr. Jahan Ara Shams; Dr. Khizar Hayat (Review Journal of Social Psychology & Social Works, 2024)
The main purpose of the current study was the exploration of parents’ experiences about early childhood education in primary schools. For this, approach of research was used as qualitative and interviews were conducted from twelve parents belongs to rural area at the government girl’s primary schools in Jhang, district Attock. The participants of the study were the parents of those students who were admitted in early childhood education in primary schools. The data were audio recorded; later on transcribed and coded. Most parents highlighted that public schools do not have enough playground facilities, and the shortage of ECE staff, which is not adequate for monitoring the performance of all children. They suggested that there should be at least one trained ECE teacher for ECE students.